Letter - Gondra, Angel de
001-0133-001 Euzkadi Ordezkaritza Basque Delegation. 7/8 Hobart Place, Eaton Square, London . S.W.1 19th January, 1944. T. Carthy, Esq. Trades Union Congress, Transport House, Smith Square, S.W.I. Dear Mr. Carthy, We have not had occasion to trouble you with our affairs for some time now, and I am glad to say that our people here are satisfactorily settled in war jobs and are doing their best to continue to help the Allies in their own capacities. The Basque Trade Union are now asking us for the names of individuals or groups at present engaged in research in connection with the post-war social reconstruction of Europe. They would particularly like to get in touch with all-Europe committees or research groups working in this country. We should appreciate it very much indeed if you could give us the names and addresses of any such bodies, official or unofficial, of which you may know and which you think would be of interest to our compatriots, so that they may approach them and co-operate with them if possible. Yours faithfully A. de Gondra 292/946/1/133